2014
DOI: 10.1186/cc13889
|View full text |Cite
|
Sign up to set email alerts
|

Management of anticoagulant-related intracranial hemorrhage: an evidence-based review

Abstract: The increased use of anticoagulants for the prevention and treatment of thromboembolic diseases has led to a rising incidence of anticoagulant-related intracranial hemorrhage (AICH) in the aging western population. High mortality accompanies this form of hemorrhagic stroke, and significant and debilitating long-term consequences plague survivors. Although management guidelines for such hemorrhages are available for the older generation anticoagulants, they are still lacking for newer agents, which are becoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 117 publications
(141 reference statements)
0
7
0
1
Order By: Relevance
“…Current guidelines therefore do not recommend its use for reversal of warfarin-related ICH. Additionally, it is 15 times more expensive than FFP and at least 3.5 times more expensive than PCC, and is associated with a higher risk of INR rebound [ 98 ]. In summary, patients with warfarin-related ICH and elevated INR should have vitamin K antagonist withheld, and should receive vitamin K (10 mg IV over 30 minutes) concomitantly with PCC guided by INR level or weighted-base dosing (20 UI/kg).…”
Section: Medical Management Of Ichmentioning
confidence: 99%
“…Current guidelines therefore do not recommend its use for reversal of warfarin-related ICH. Additionally, it is 15 times more expensive than FFP and at least 3.5 times more expensive than PCC, and is associated with a higher risk of INR rebound [ 98 ]. In summary, patients with warfarin-related ICH and elevated INR should have vitamin K antagonist withheld, and should receive vitamin K (10 mg IV over 30 minutes) concomitantly with PCC guided by INR level or weighted-base dosing (20 UI/kg).…”
Section: Medical Management Of Ichmentioning
confidence: 99%
“…An increased risk of anticoagulantassociated intracranial hemorrhage (AICH) was observed in patients with thromboembolic disease receiving anticoagulant therapy. Especially with warfarin, when the INR is between 2-4.5, the risk of AICH is 0.3 to 3.7% (Ray and Keyrouz, 2014). Due to the high risk of anticoagulation which can cause hematoma expansion and high morbidity due to warfarin-related intracerebral hemorrhage (WRICH), anticoagulation is recommended to be temporarily discontinued during the acute phase of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the RE-COVER trial, which compared dabigatran and warfarin in acute venous thromboembolism, reported no incidence of ICH during 6 months of therapy, ROCKET-AF reported that the ICH incidence was 0.49% for rivaroxaban compared to 0.74% for warfarin. 37 A recent prospective observational study reported that DOAC-ICH was associated with smaller ICH volume and better clinical outcome, when compared to warfarin-ICH. 38 However, these findings have not been confirmed by further observational studies.…”
Section: During Doacs Therapymentioning
confidence: 99%